The Assessment Of Energy And Protein Needs Coverage In Hospitalized Patients - Pandel Mikuš Ruža; Vičič Vid; Dahmane Raja (Sciendo, 2016)
Aiming at assessing sufficiency of energy/protein intake in hospitalized patients, the objective was to monitor and analyze actual food intake of patients hospitalized in three clinical wards of one of major Slovenian hospitals.